Seismic performance and fragility analysis of power distribution concrete poles. Issue 150 (November 2021) - Baghmisheh, Amir Ghahremani; Mahsuli, Mojtaba
Abstract: This paper proposes probabilistic damage and collapse models for reinforced concrete poles in electric power distribution networks and investigates the damage and collapse pattern of poles under earthquake excitations. To this end, detailed finite element models of the H-type reinforced concrete poles are developed and verified using past experimental studies as well as the observed damage in previous earthquakes. The models are then subjected to nonlinear static analyses to study the effect of the loading pattern, loading direction, concrete strength, and failure criteria on the capacity and the collapse pattern of the pole. Next, incremental dynamic analysis is carried out to investigate the sensitivity of the seismic response and collapse pattern of the pole to the direction of ground motion, record-to-record variability, and concrete strength. The results show that the damage pattern under static pull tests, which are the only type of the test conducted on such poles, poorly represent the seismic collapse pattern of the pole. The results also reveal that the most vulnerable segment of the pole is the first 0.5 m of the pole above the ground, which can guide the future retrofit strategies. The results of the incremental dynamic analysis are subsequently employed to develop damage and collapse fragility models for 9, 12, and 15 m long poles using the maximum likelihood method. The analysis accounts for the uncertainty not only in the ground motion but also in the material properties of poles. The proposed models make it possible to account for the damage incurred by the power distribution lines in the seismic risk analysis of the power distribution networks as well as the seismic resilience analysis of electrified communities. Highlights: Detailed finite element model of poles is developed and verified by real-world observations. Effects of various parameters on the collapse pattern of poles is studied by sensitivity analysis. It is shown that static pull tests poorly represent the seismic performance of poles. Incremental dynamic analysis reveals the most vulnerable segment of poles. Damage and collapse fragility models are proposed for risk and resilience analysis of power networks.